2009
DOI: 10.1099/mic.0.027532-0
|View full text |Cite|
|
Sign up to set email alerts
|

Bmh1p (14-3-3) mediates pathways associated with virulence in Candida albicans

Abstract: The ability of the pathogenic fungus Candida albicans to cause disease requires rapid adaptation to changes in the host environment and to an evolving host immune response. The identification of 'virulence factors' using in vitro characterization of mutant strains has traditionally relied on a common set of phenotypic and biochemical assays (most often performed at 30 6C) and the subsequent correlation with their corresponding virulence in mouse models of disease. Utilizing a panel of isogenic mutants for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…More importantly, the fungal‐killing action irrespective of culticular or cuticle‐bypassing infection was delayed by ∌50% in our deletion and deletion/silence mutants, an indication of attenuated virulence as seen in the Δ Bmh1 mutant of C. albican s (Kelly et al ., ). This could be partially attributable to their slower growth and perturbed cell cycle, as clued by fewer blastospores formed in host haemolymph ∌4 days after infection.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the fungal‐killing action irrespective of culticular or cuticle‐bypassing infection was delayed by ∌50% in our deletion and deletion/silence mutants, an indication of attenuated virulence as seen in the Δ Bmh1 mutant of C. albican s (Kelly et al ., ). This could be partially attributable to their slower growth and perturbed cell cycle, as clued by fewer blastospores formed in host haemolymph ∌4 days after infection.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence now is emerging that demonstrates the differential expression patterns of 14-3-3 in healthy controls verses patients with aliments such as joint inflammation [54], multiple sclerosis [55–56] and endometriosis [57]. Furthermore, studies have revealed abnormalities in signaling mediated by 14-3-3 in diseases such as glaucoma [58], phospholipidosis [59] and infectious diseases [60–61]. It appears that altered interactions between 14-3-3 and client proteins may be responsible for a variety of dieases.…”
Section: 14-3-3 In Human Diseasesmentioning
confidence: 99%
“…In Saccharomyces cerevisiae, two 14-3-3 genes, BMH1 and BMH2 [39], are required for multiple functions, including several downstream events of the RAS-mediated pathway [40], exocytosis, and vesicular transport steps [11]. In Candida albicans, its 14-3-3 protein is required for vegetative growth and optimal filamentation, suggesting its role in the regulatory pathways required for colonization and invasion [21]. As the 14-3-3 protein has multiple roles in different organisms and because of its abundance in the CnMVs, we are interested to know whether the C. neoformans 14-3-3 protein plays any pathological role during infection.…”
Section: Introductionmentioning
confidence: 99%